Предмет: Алгебра, автор: Ulana105

Решить уравнение 2^x+5 - 3^x+3 = 2^x+1 + 6*3^x+1

Ответы

Автор ответа: Аноним
4

2^{x+5} - 3^{x+3} = 2^{x+1}+6*3^{x+1}

2^{x} * 2^{5} - 3^{x} * 3^{3}=2^{x} * 2 + 6 *3^{x} *3

2^{x} * 32-3^{x} * 27 = 2 * 2^{x} + 18 * 3^{x}

32 * 2^{x} - 27 * 3^{x} = 2*2^{x} + 18 * 3^{x}

32*2^{x} - 2 * 2^{x}= 18 * 3^{x} + 27 * 3^{x}

30 * 2^{x} = 45 * 3^{x}

30*(\frac{2}{3})^{x} = 45

(\frac{2}{3})^{x}=\frac{3}{2}

(\frac{2}{3})^{x} = (\frac{2}{3})^{-1}

x=-1

Похожие вопросы
Предмет: Русский язык, автор: ananinaangelina1